Staff perceptions of challenging parent–staff interactions and beneficial strategies in the Neonatal Intensive Care Unit. (12th September 2017) - Friedman, Joshua; Friedman, Susan Hatters; Collin, Marc; Martin, Richard J.
Abstract: Aim: To characterise neonatal intensive care unit (NICU) staff perceptions regarding factors which may lead to more challenging staff–parent interactions, and beneficial strategies for working with families with whom such interactions occur. Methods: A survey of 168 physician and nursing staff at two NICUs in American teaching hospitals inquired about their perceptions of challenging parent–staff interactions and situations in which such interactions were likely to occur. Results: From a medical perspective, staff perceptions of challenging interactions were noted when infants had recent decompensation, high medical complexity, malformations or long duration of stay in the NICU. From a psychological/social perspective, a high likelihood of challenging interactions was noted with parents who were suspicious, interfere with equipment, or parents who hover in the NICU, express paranoid or delusional thoughts, repeat questions, perceive the staff as inaccessible, are managing addictions, or who require child protective services involvement. Frequent family meetings, grieving opportunities, education of parents, social work referrals, clearly defined rules, partnering in daily care and support groups were perceived as the most beneficial strategies for improving difficult interactions. Conclusion: This study delineates what staff perceive as challenging interactions and provides support for an educational and interventional role that incorporates mental health professionals. Abstract :